2016
DOI: 10.1093/cvr/cvw062
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of phosphate-induced osteo-/chondrogenic transformation of vascular smooth muscle cells by homoarginine

Abstract: Homoarginine augments osteo-/chondrogenic transformation of VSMCs and vascular calcification, effects involving impaired NO formation from homoarginine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
82
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 48 publications
0
82
0
Order By: Relevance
“…The origin of these mice was described previously (22). Subtotal nephrectomy was performed during isoflurane anesthesia (1.5%-2%) as previously described (6). In a first step, the right kidney mass was reduced by electrocauterization and surgical excision.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The origin of these mice was described previously (22). Subtotal nephrectomy was performed during isoflurane anesthesia (1.5%-2%) as previously described (6). In a first step, the right kidney mass was reduced by electrocauterization and surgical excision.…”
Section: Methodsmentioning
confidence: 99%
“…MAoSMCs were grown to confluence in DMEM/F12 medium (Thermo Fisher Scientific) supplemented with 10% FBS (Thermo Fisher Scientific), 100 U/ ml penicillin, 100 μg/ml streptomycin (Thermo Fisher Scientific), and 0.025 μg/ml Fungizone (Thermo Fisher Scientific). The cells were used in all experiments from passages [3][4][5][6]. N indicates the number of independent experiments from 3 independent isolations of MAoSMCs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…34 These processes promote VSMC transformation with vascular calcification and have been linked to impaired NO formation and homoarginine. 35 NO can inhibit NADPH oxidases. 36 Gao et al demonstrated a potentially important practical application of this observation to explain the mechanism by which dietary nitrate reduces BP.…”
mentioning
confidence: 99%